1991
DOI: 10.2134/jpa1991.0260
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficit Effects on the Cotton Leaf Cuticle and the Efficiency of Defoliants

Abstract: Inconsistent results are often experienced with chemical defoliants in cotton (Gossypium hirsutum L.). Leaves of field‐and growth chamber‐grown plants were used in a 3‐yr study to evaluate the hypothesis that drought‐induced alterations in the leaf cuticle may be associated with the decreased efficiency of defoliants. Plants which experienced previous water stress had reduced defoliation and increased regrowth when treated with the commercial defoliant Harvade [dimethipim (2,3 dihydro‐5,6‐dimethyl‐1,4‐dithiin‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…The results of this study reinforce the results by Retzlaff (1983), but also suggest that the quantity of ECW may affect bentazon absorption as the quantity of ECW was greater under the DS condition. Oosterhuis et al (1991) concluded that an increase in leaf ECW production for cotton was associated with decreased foliar-applied chemical penetration.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study reinforce the results by Retzlaff (1983), but also suggest that the quantity of ECW may affect bentazon absorption as the quantity of ECW was greater under the DS condition. Oosterhuis et al (1991) concluded that an increase in leaf ECW production for cotton was associated with decreased foliar-applied chemical penetration.…”
Section: Resultsmentioning
confidence: 99%
“…Jordan et al (1984) reported that sorghum leaf wax densities Ͼ 0.07 g/m 2 were effective in reducing cuticular water loss under most conditions. Water-stressed cotton leaves were found to have altered wax composition, greater cuticle thickness, and increased wax content, which collectively decreased penetration of chemical leaf defoliant (Oosterhuis, Hampton, and Wullschleger, 1991). Bondada et al (1996) found that water-stressed cotton leaves had altered wax composition and increased wax content (leaves, bolls, and bract), but no discernible changes in wax morphology were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Dicamba and 2,4-D are systemic herbicides and efficacy is dependent on translocation within the plant [35]. Larger plants may have thicker plant cuticles which could reduce herbicide penetration resulting in poor control [27,36,39]. Furthermore, mature plants have reduced sugar transport which may decrease translocation of some systemic herbicides [34,40,41].…”
Section: Field Study: Dicamba-based Programsmentioning
confidence: 99%